Ensuring the Sustainable Availability of Affordable Quality Seeds and Planting Materials in Uganda - Naluwairo, Ronald; Barungi, Julian (ACODE, 2014)
The availability and use of quality seeds and planting materials in Uganda remains very low. The use of quality seeds is estimated at just between 10-15 per cent. This is inspite of the fact that the use of quality seeds and planting materials is key in increasing agricultural production and productivity. Explanations for the low availability and low use of quality seeds and planting materials in Uganda include: insufficient breeder and basic seed classes for many varieties; insufficient field supervision and inspection services leading to lack of quality control along the entire seed value chain; and limited capacities in the seed industry especially in the area of research & innovation, and infrastructure for seed production and conditioning. Other reasons include: the lack of seed data to project national seed demand for national planning and forecasting of various seed types that farmers need; high cost of quality seeds; limited farmer awareness; inefficient and ineffective institutional setup and absence of a seed policy.